Application of geoelectrical techniques in the investigation of a coastal sand dune field - Alexopoulos, J.D.; Dilalos, S.; Poulos, S.; Ghionis, G.; Mavroulis, S. (20th European Meeting of Environmental and Engineering Geophysics, 2014)
<span style="color: #677078; font-family: Roboto, Verdana, Trebuchet, Helvetica, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">A geophysical research was carried out to investigate the lithostarigraphic substratum characteristics of the dune field of the central Kyparissiakos Gulf (W. Peloponnese, Greece), which is characterised by the presence of four dune lines. For this purpose, the geophysical techniques of Electrical Resistivity Tomography (ERT) and Vertical Electrical Soundings (VES) were applied, along with detailed morphological mapping and the collection of geological and geomorphological information. The processing of the geophysical data that were collected from two ERT soundings, perpendicular to the general direction of the dune lines, and seven geoelectrical soundings revealed four geoelectrical layers with the two surficial resistive layers adumbrating the extent and thickness of the four sand dune ridges and the associated slags. The third layer, corresponding to the underlying geoelectrical formation of 50–75 Ohm.m, is interpreted as a layer of transgressive Holocene deposits saturated with fresh water, while the deepest geoelectrically identified layer seems to correspond to the “Neda” formation, which consists of marls, sandy marls and conglomerates. It is concluded that the combined application of the aforementioned techniques has the potential to provide valuable data for the investigation of complex coastal depositional environments.